The vision of the sacred to the millennials: the idolatry of the Youtubers (Journal of the Sociology and Theory of Religion, 2019)
The heroes of children’s imaginary lay on different social and cultural paradigms, yet sharing a few common traits, such as the strength of extraordinary super powers, the duality of good and evil, the relation between cosmic elements and between what is human and inhuman. These heroes go from the god-man in the classics of the Greeks, to the messianic figure in a Judaeo-Christian point of view, from the mythic characters of fairy tales made eternal by the cinematographic industry, to the technological versions of heroes as Pokemons or even more bionic types.Recently, there seems to be emerging a new type of hero to the millennials, which is the Youtuber character. This research is based on the representations that children aged between 9 and 13 years old have of the Youtubers. The sample consists of children studying in a Portuguese public school to whom we have applied an online questionnaire.
Keywords: sacred; Youtuber; idolatry; hero; millennials